(untitled) (Journal of actual problems of jurisprudence, 2019)
The article examines the processes of development of the right of citizens to a healthy environment in Kazakhstan. A few decades ago, the right to a safe and supportive environment was not aware of legal science. Appeared in the twentieth century, it was quick in its development, because of the global environmental problems that contributed to the strengthening of its status, which allowed the transfer to basic rights such as the right to life. The study shows the development of the regulatory framework of the Kazakh SSR, Soviet Union and for the protection of the environment and environmental policy inefficiency of the Soviet period, due to the extensive activities of the USSR, which inflicted irreparable damage to the environment in Kazakhstan. Keywords: right to a healthy environment, history of development of the right of Kazakhstan, international acts.